Human resources development based on total quality management at Titik Balik Coffee Shop - Nugraha, Alifian; Rohim, Rohim; Cahyo, Dawut Nur (Institute of Computer Science (IOCS), 2025)
The importance of Human Resource Development (HRD) and Total Quality Management (TQM) for business success, particularly in the service sector like cafes and coffee shops. In a competitive environment, service quality is crucial, and effective HR management directly influences customer satisfaction and profitability. TQM, a managerial approach focusing on continuous quality improvement, requires commitment from all employees, not just top management, to be effective. The coffee shop industry in Indonesia, especially in Jember Regency, faces challenges in maintaining service consistency due to employee performance variations. TQM can address these issues by reducing variation, improving HR performance, and ensuring consistent service. However, the adoption of TQM faces obstacles, including a lack of understanding of TQM principles, resistance to change, and limited resources for training. Overcoming these barriers requires adequate training, strong management support, and financial investment. The study emphasizes that implementing TQM in human resource development can enhance service quality and competitiveness, especially through performance evaluation, training, and motivation.